Application of Silicon Nanostructure Arrays for 6-inch Mono and Multi-Crystalline Solar Cell - Chen-Chih Hsueh (Nanoscale Research Letters, 2019)
Abstract In this study, we fabricate uniform silicon nanowire (SiNW) arrays on 6-inch mono- and multi-crystalline wafers by employing the improved solution-processed metal-assisted chemical etching (MacEtch) method. Furthermore, the improved MacEtch can be applied to various crystalline orientation wafers. The SiNW arrays are 470 nm in length with high density; they demonstrate a good optical trapping effect and reflectance well below 6% over a broad wavelength range from 300 to 1100 nm. The improved MacEtch shows no difference in reflectance for a pyramid/SiNW mono-crystalline wafer with appropriate uniformity; the average delta from the center to other positions is within 22%. The effective lifetime is lower for SiNW arrays because the higher surface state causes higher surface recombination. Finally, we make the multi-crystalline wafer into an Al-BSF solar cell device with MacEtch SiNW texture, resulting in an averaged power conversion efficiency of 17.83%, which is higher than that of standard acid-textured solar cell devices. Consequently, the improved MacEtch concept is suitable for commercial mass production in the photovoltaic industry.